2020
DOI: 10.2478/gp-2020-0014
|View full text |Cite
|
Sign up to set email alerts
|

Physician Suicide: A Scoping Literature Review to Highlight Opportunities for Prevention

Abstract: AbstractObjective:The aim of this scoping review is to map the current landscape of published research and perspectives on physician suicide. Findings could serve as a roadmap for further investigations and potentially inform efforts to prevent physician suicide.Methods:Ovid MEDLINE, PsycINFO, and Scopus were searched for English-language publications from August 21, 2017 through A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 253 publications
0
10
0
Order By: Relevance
“…A previous scoping review of the literature about physician suicide identified articles that commented on or investigated suicidal behaviors of physician populations, including students, postgraduate trainees, and practicing physicians [ 7 ]. Briefly, in that literature review, a medical librarian assisted in refining the research question, developing the search strategy, and conducting a search of relevant electronic databases, including Ovid Medline, PsycINFO, and Scopus.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A previous scoping review of the literature about physician suicide identified articles that commented on or investigated suicidal behaviors of physician populations, including students, postgraduate trainees, and practicing physicians [ 7 ]. Briefly, in that literature review, a medical librarian assisted in refining the research question, developing the search strategy, and conducting a search of relevant electronic databases, including Ovid Medline, PsycINFO, and Scopus.…”
Section: Methodsmentioning
confidence: 99%
“…These databases were searched from inception through April 2018. Using the predefined literature review methodology, 347 articles were identified for analysis, with the earliest dating back to 1903 [ 7 ]. From these 347 articles, articles were further screened for this proof-of-concept study to focus on articles that made an assertion, or claim, about the annual rate of US physicians who die of suicide.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rates of suicide due to overdose are also likely to be higher among physicians, as compared with general population. Even among physicians, rates of suicide vary depending on gender, region religion, and branch/specialty (Hikiji & Fukunaga, 2014; Leung et al, 2020; Malone et al, 2021). Suicide prevention efforts targeted at physicians should recognize, understand, and take care of such differences, which may translate into development of effective targeted interventions that include personalized interventions designed to address individual risk profile (Center et al, 2003).…”
Section: Recommendationsmentioning
confidence: 99%